Pleuroscopy in Undiagnosed Exudative Pleural Effusion, Early Experience in Bangladesh (Chest & Heart Journal, 2021)
Background: Rigid pleuroscopy is an accurate diagnostic method for undiagnostic exudative pleural effusion which is a burden in our country.Methods and Materials: It was a prospective study done in dept. of Thoracic surgery, Dhaka Medical College Hospital (DMCH), Bangladesh, from 1st July 2018 to 30th June 2019 and total 46 patients with undiagnosed exudative pleural effusion were selected and rigid pleuroscopy performed to obtain biopsy.Results: Rigid pleuroscopy showed diagnostic accuracy of 95.7% with minimal complications (6.4%). As visualization is also a part of this procedure it gives an additional strength in the diagnosis which proved to be 100% accurate.Conclusion: It is an excellent diagnostic tool which is accurate, easy to perform, with least complications and less time consuming, so patient turnover is better which is of great advantage in our country.Chest Heart J. 2020; 44(2) : 68-72